Pumps - Smith, Peter; Cotton Research and Development Corporation (Australia); New South Wales. Department of Primary Industries ([Narrabri, N.S.W.] : Cotton Research & Development Corporation, 2007)
"The information in this publication is designed as an information source to improve the sustainable use of water on irrigation farms in eastern Australia growing cotton."--Verso cover.
Caption title.
"First edition: November 2007"--Cover verso.
Logos of NSW Department of Primary Industries, National Program for Sustainable Irrigation, Cotton Research & Development Corporation, GRDC, Qld. Dept. of Primary Industries and Fisheries, Cotton Catchment Communities CRC, and Cooperative Research centre for Irrigation Futures on back cover.
"First edition: November 2007"--Verso cover.
Keywords: Irrigation pumps -- Evaluation; Irrigation pumps -- Econometric models; Cotton -- Irrigation -- Australia -- Equipment and supplies